Suplementasi Tepung Putih Telur untuk Memperbaiki Nilai Nutrisi Snack Ekstrusi Berbahan Grits Jagung - . Budiman; Z Wulandari; T Suryati (Media Peternakan, 2009)
Snack is popular for children and adult. It could be made by extrusion process. Snack is low in protein content because it is made up of cereal such as rice and corn. On the basis of nutritional and functional properties, egg was used in food industries. The objectives of the research were to analyze the nutrient content and in vitro digestibility of extruded snack from corn grits which was supplemented by egg white powder as a protein source. Randomized complete block design was used in this experiment with production periods as block. Water content was not significantly different between treatments. Supplementation with 10% egg white powder significantly increased the fat content of extrusion snack. Protein content and digestible protein increased significantly as increasing of egg white powder added. Protein digestibility of products with 10%, 15%, and 20% of egg white addition was significantly lower than those added with 0% and 5% egg white. Protein, fat, and carbohydrate linkage had formed porous product. This linkage affects product nutritive content and digestibility. Key words: egg, corn, extrusion, snack, digestibility